Klasse Walter Dahn : Make my paper sound. - Kunstverein Braunschweig, Braunschweig; Adamopoulos, Konstantin; Brandes, Hanna; Braun, Anne; Dahn, Walter; Danyel, Joachim, W.; Eure, Carina; Gehlen, Andreas; Grässlin, Karola; Janik, Daniel; Kunath, Friedrich, E.; Lindena, Kalin; et al. (Braunschweig : Kunstverein Braunschweig e.V., 2000)
Bauer, Michael ; Bell, Dirk ; Brandes, Hanna ; Braun, Anne ; Dahn, Walter ; Danyel, Joachim W. ; Dickreiter, Jo ; Gehlen, Andreas ; Geipel, Björn ; Hartmann, Kirsten ; Janik, Daniel ; Kristen, Hardy ; Kunath, Friedrich E. ; Lindena, Kalin ; Maiwald, Phillip ; Müller, Nalan ; Popp, Stefanie ; Schiffers, Antje ; Seipp, Marc-A. ; Sicoli, Silvina ; Tobias, Gert ; Tobias, Uwe ; Uhlig, Michael ; Werner, Chiara
Duits
Make my paper sound, Kunstverein Braunschweig e.V., Braunschweig, 05. Februar bis 26. März 2000
boek